Using Multiple Choice Questions Written at Various Bloom's Taxonomy Levels to Evaluate Student Performance across a Therapeutics Sequence - Amy M. Tiemeier, Pharm.D., BCPS; Zachary A. Stacy, Pharm.D., BCPS; John M. Burke, Pharm.D., FCCP, BCPS (University of Minnesota Libraries Publishing, 2011)
Objective: To evaluate the results of a prospectively developed plan for using multiple choice questions (MCQs) developed at defined Bloom's levels to assess student performance across a Therapeutics sequence.Methods: Faculty were prospectively instructed to prepare a specific number of MCQs for exams in a Therapeutics sequence. Questions were distributed into one of three cognitive levels based on a modified Bloom's taxonomy, including recall, application, and analysis. Student performance on MCQs was compared between and within each Bloom's level throughout the Therapeutics sequence. In addition, correlations between MCQ performance and case performance were assessed.Results: A total of 168 pharmacy students were prospectively followed in a Therapeutics sequence over two years. The overall average MCQ score on 10 exams was 68.8%. A significant difference in student performance was observed between recall, application, and analysis domain averages (73.1%, 70.2% and 60.1%; p<0.001). Student performance within each Bloom's level across the three courses was significantly different for recall (p<0.001), application (p<0.001), and analysis (p<0.001) MCQs. A significant correlation was observed between the recall domain and the case (0.67; p<0.01), application domain and the case (0.62; p<0.01), and analysis domain and the case (0.64; p<0.01).Conclusions: As students progress through the curriculum, faculty may need to find ways to promote recall knowledge for more advanced topics while continuing to develop their ability to apply and analyze information. Exams with well-designed MCQs that prospectively target various cognitive levels can facilitate assessment of student performance.